The Effect of Flat-Type and L-Type Checkout Counters on Customer's Perceptual and Functional Evaluations - Subasi, Tolga; Yildirim, Kemal; Muezzinoglu, Mensure Kubra (Konya Technical Univ, Fac Architecture & Design, 2025)
This study aims to determine the effects of physical environmental factors in markets, which are an integral part of daily life, on perceptual and functional evaluations of participants. In this study, it is thought that physical environmental factors in supermarkets where flat-type and L-type checkout counters are used may positively or negatively affect customers' perceptual and functional evaluations. The research hypotheses focus on the correlations with the independent variables of checkout counter type, gender, and age. The & Ccedil;a & gbreve;da & scedil; Grocery Stores were selected as the research environment and an evaluation questionnaire on the environmental factors of the stores was applied to 200 customers who shopped at these stores. The questionnaire results show that the L-type checkout counter is found to be more aesthetic, inviting, organized, functional, and useful by customers compared to the flattype counter. These results show that the design of the checkout counter plays a critical role in customer satisfaction and user experience. Therefore, it was concluded that the checkout counter type can be an important design criterion for improving the shopping experience in markets. This study undertaken emphasizes the critical role played for customer satisfaction and service quality in the retail sector area of operations and checkout counters and stresses the importance of design characteristics in this field. Enterprises can take steps to improve the shopping experience by revising their checkout counter preferences in accordance with the expectations and needs of customers.
Keywords: Cash register; Checkout counter; Perception; Shopping decisions; Supermarket